Managing Global Issues : Lessons Learned - Mathews, Jessica Tuchman; Jonge Oudraat, Chantal de; Simmons, P. J., 1967- (Book collections on Project MUSE., 2001)
Globalization is pushing to the fore a wide variety of global problems that demand urgent policy attention. Managing Global Issues provides a comprehensive comparative assessment of international efforts to manage global problems. It identifies and explains successes and failures of such efforts, examines the roles of different actors, and outlines lessons that may guide future action by governments, international organizations, nongovernmental organizations, and the private sector. The volume's 16 case studies examine organized crime, drugs, corruption, human rights, labor rights, health, trade, financial markets, development assistance, the environment, the global commons, communications, weapons of mass destruction, conventional weapons, internal conflicts, and refugees. Managing Global Issues is the result of an international multidisciplinary research team composed of experts in specific global issue areas. The book's broad scope, numerous case studies and its rigorous comparative analytical framework offers a unique and valuable contribution to the rapidly growing literature on global governance. Contributors include Vinod K. Aggarwal (University of California, Berkeley), Thomas Bernauer (University of ZUrich), William Drake (Carnegie Endowment), Octavio GOmez-DantEs (National Institute of Public Health, Mexico), Catherine Gwin (World Bank), Peter M. Haas (University of Massachusetts, Amherst), Christopher C. Joyner (Georgetown University), Brian Langille (University of Toronto), Robert E. Litan (Brookings Institution), Kathleen Newland (Carnegie Endowment), Peter Richardson (Transparency International), Peter H. Sand (Institute of International Law, Munich), Dinah L. Shelton (Notre Dame Law School), Timothy D. Sisk (University of Denver), Joanna Spear (King's College, London), and Phil Williams (University of Pittsburgh).